Jellyfish blooms through the microbial lens: temporal changes, cross-species and Jellyfish-water comparisons - Noga Barak; Vera Brekhman; Dikla Aharonovich; Tamar Lotan; Daniel Sher (Environmental Microbiome)
Abstract Jellyfish blooms have significant ecological and economic impacts, yet the microbial communities associated with these blooms remain poorly understood, despite their potential influence on host fitness and microbial communities in the surrounding water. In this study, we explored temporal and tissue-specific variations in the microbiota of Rhopilema nomadica, the dominant jellyfish species in the Eastern Mediterranean Sea, across winter and summer blooms. During late summer blooms, microbial richness declined, coinciding with an increase in Endozoicomonas and unclassified Rickettsiales, while Tenacibaculum predominantly characterized winter blooms. Tissue-specific analyses revealed bacterial groups that were more consistently associated with different jellyfish tissues (e.g., Bacteroides in the bell and Simkaniaceae in the gonads), suggesting different microbial niches within the host. Furthermore, some key bacteria associated with R. nomadica, including Endozoicomonas, unclassified Rickettsiales, and Bacteroides were detected in the surrounding bloom water but absent from remote seawater, suggesting potential localized transmission dynamics between jellyfish and their immediate marine environment. Finally, a comparative analysis with nine additional jellyfish species identified recurring microbial taxa, including Endozoicomonas, Mycoplasma, and Spiroplasma, though no universal core microbiota was observed. This study represents the first exploration of microbial dynamics within R. nomadica blooms and the most comprehensive analysis of jellyfish-associated microbiomes across bloom stages and tissues to date. Our findings reveal complex relationships between jellyfish species, bloom progression, their microbial communities, and the surrounding seawater.